PDCT-03. CHEMOTHERAPY STRATEGIES FOR YOUNG CHILDREN NEWLY DIAGNOSED WITH MEDULLOBLASTOMA UP TO THE ERA OF MOLECULAR PROFILING – A COMPARATIVE OUTCOMES ANALYSIS. (11th November 2019) - Finlay, Jonathan; Mynarek, Martin; Dhall, Girish; Lafay-Cousin, Lucie; Mazewski, Claire; Ashley, David; Leary, Sarah; von Bueren, Andre; Gerber, Nicolas; Cohen, Bruce; Robinson, Giles; Russell Geyer, J; et al.
Abstract: BACKGROUND/OBJECTIVE: Survival had been poor in several multi-center/national studies since the 1980s attempting to delay, avoid or minimize brain irradiation in young children with medulloblastoma. The introduction of regimens in Germany incorporating both intravenous high-dose (HD-MTX) and intraventricular (IVENT-MTX) methotrexate, as well as regimens in North America incorporating marrow-ablative chemotherapy with autologous hematopoietic cell rescue (HDCx+AuHCR), have reported encouraging outcomes. The objective of this report is to perform a comparative outcomes analysis of these differing strategies. METHODS: Data from 17 prospective multi-center trials published between 1990 and 2018 for children under six years old with medulloblastoma were reviewed; event-free (EFS) and overall survivals (OS) were compared. RESULTS: Two trials using full-dose cranio-spinal irradiation with or without chemotherapy reported 5-year survivals of 32–38%. Three trials using standard chemotherapy with delayed irradiation reported 2-4-year EFS and OS of 23–34% and 31–46%. Two trials employing standard chemotherapy without irradiation reported 3-5-year EFS and OS of 22–33% and 34–43%. Four trials incorporating HD-MTX with or without IVENT-MTX reported 5-10-year EFS and OS of 56–59% and 67–80%, and 31% and 59% respectively; one trial with HD-MTX without IVENT-MTX for localized desmoplastic/nodular medulloblastoma (DN-MB) reported 2-year EFS and OS of 52% and 92%. Finally, five trials employing induction chemotherapy, with or without HD-MTX, followed by single or tandem HDCx+AuHCR have reported 3-5-year EFS and OS of 45–60% and 60–70%. CONCLUSIONS: The best survivals are observed in trials including HD-MTX and IVENT-MTX or including HD-MTX during induction followed by HDCx+AuHCR. Because histology/biology (classic and large cell/anaplastic versus DN-MB; SHH versus non-SHH subtypes) have crucial prognostic roles, EFS and irradiation-free survival advantages require analysis in these settings. The benefit of these trials appears true for all young children with medulloblastoma. Risk-adapted treatment stratification for young children may be improved by molecular profiling of SHH- and non-SHH medulloblastoma.